Prosiding Seminar Warisan Melayu dan Peribumi, 13 September 2005 - Seminar Warisan Melayu dan Peribumi ( 2005 : Serdang, Selangor).; Universiti Putra Malaysia. Unit Dokumentasi Warisan Melayu dan Peribumi; Malaysia. Jabatan Muzium ([Serdang] : Unit Dokumentasi Warisan Melayu dan Peribumi, Fakulti Bahasa Moden dan Komunikasi, UPM, 2005)
History and customs of Malay people in Thailand & South Africa and the influence of Thai and Afrikaans languages on Malay language.
Keywords: Malays (Asian people) -- Thailand -- History -- Congresses; Malays (Asian people) -- South Africa -- History -- Congresses; Malays (Asian people) -- Thailand -- Social life and customs -- Congresses; Malays (Asian people) -- South Africa -- Social life and customs -- Congresses; Thai language -- Influence on Malay -- Congresses; Afrikaans language -- Influence on Malay -- Congresses